2016
DOI: 10.1080/17501229.2015.1120736
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the global orientation of English textbooks in Germany

Abstract: This article investigates textbooks used in English classes in German schools to evaluate their relevance to current trends of teaching English as an international language. For many European students, English is no longer just a foreign language, but an important European lingua franca. Thus, we argue it is essential for the language to be positioned as such in key textbooks used in English classrooms, which aim to prepare students for future use of English. An analysis of three main textbook series used in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 22 publications
6
57
1
Order By: Relevance
“…This means that the third hypothesis suggesting British English prevalence in the domain of grammar was refuted. Despite the fact that British English seems to receive a stronger institutional support, in particular through school textbooks and all school-related material (Bieswanger, 2008;Dazdarević, 2007;Grubor et al, 2008;Grubor & Hinić, 2011;Imamović & Delibegović-Džanić, 2016;Mair, 2013;Proshina, 2006;Syrbe & Rose, 2016, Trudgill & Hannah, 2013, our findings appear to be similar to those reported in Grubor et al (2008), which showed that both students and teachers use the grammatical structures common to American English more frequently than the related ones in British English. Although most school textbooks seem to suggest using the present perfect tense in the contexts provided in the survey, our research results clearly indicate a greater usage of the Past Simple Tense by our participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the third hypothesis suggesting British English prevalence in the domain of grammar was refuted. Despite the fact that British English seems to receive a stronger institutional support, in particular through school textbooks and all school-related material (Bieswanger, 2008;Dazdarević, 2007;Grubor et al, 2008;Grubor & Hinić, 2011;Imamović & Delibegović-Džanić, 2016;Mair, 2013;Proshina, 2006;Syrbe & Rose, 2016, Trudgill & Hannah, 2013, our findings appear to be similar to those reported in Grubor et al (2008), which showed that both students and teachers use the grammatical structures common to American English more frequently than the related ones in British English. Although most school textbooks seem to suggest using the present perfect tense in the contexts provided in the survey, our research results clearly indicate a greater usage of the Past Simple Tense by our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that British English receives stronger institutional support through foreign language teaching and is widely present in the school textbooks and other related material (Bieswanger, 2008;Dazdarević, 2007;Grubor et al, 2008;Mair, 2013;Grubor & Hinić, 2011;Proshina, 2006;Syrbe & Rose, 2016, Trudgill & Hannah, 2013, we expect that Bosnian university-level students would resort to using the British variety more frequently than the American variety in the aspect of grammar.…”
Section: H3mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures depicted are from the inner circle with few exceptions, such as India and South Africa (Syrbe & Rose, 2016). Cultures depicted are from the inner circle with few exceptions, such as India and South Africa (Syrbe & Rose, 2016).…”
Section: Competencesmentioning
confidence: 99%
“…Though it seems that there is a focus on native speaker varieties, this idea is essential to introducing higher diversity of English varieties into ELT, as proposed by EIL-oriented teaching scholars (McKay, 2012). In an analysis of English textbooks used in NRW's Gymnasium, (Syrbe & Rose, 2016) found that the varieties presented were restricted to American and British English, with only a few exceptions. While these exceptions show a positive trend, teachers will need to find alternative sources when wishing to introduce their students to the diversity of English.…”
Section: Varietiesmentioning
confidence: 99%